Improved outcome at end of treatment in the collaborative Wilms tumour Africa project. Issue 5 (19th January 2018) - Israels, Trijn; Paintsil, Vivian; Nyirenda, Dalida; Kouya, Francine; Mbah Afungchwi, Glenn; Hesseling, Peter; Tump, Clara; Kaspers, Gertjan; Burns, Liz; Singh Arora, Ramandeep; Chagaluka, George; Nana, Philippa; et al.
Abstract: Background: The Collaborative Wilms Tumour (WT) Africa Project has implemented an adapted WT treatment guideline in sub‐Saharan Africa as a multi‐centre prospective clinical trial. A retrospective, baseline evaluation of end‐of‐treatment outcome was performed for a 2‐year period prior to the introduction of this guideline. The collaborative project aims to reduce both treatment abandonment and death during treatment to less than 10% for improving survival. Procedure: All participating centres obtained local Institutional Research Board (IRB) approval and implemented the adapted WT treatment guideline. End‐of‐treatment outcome was documented for 2 years. It was divided into alive without evidence of disease, treatment abandonment, death during treatment and persistent disease. The outcome of children enroled in the first 2 years of the prospective clinical trial has been compared to the outcome before the start of the project. Results: One hundred twenty‐two patients were included in the baseline evaluation (2011–2012) and 133 in the first 2 years of the collaborative clinical trial (2014–2015). The percentage of patients alive without evidence of disease at the end of treatment increased from 52% (63/122) to 68% (90/133; P  = 0.01). Treatment abandonment decreased from 23% (28/122) to 13% (17/133; P  = 0.03). Death during treatment decreased from 21% (26/122) to 13% (17/133; P  = 0.07). Conclusion: This collaboration, using relatively simple and low‐cost interventions, led to a significant decrease in treatment abandonment and increase in survival without evidence of disease at the end of treatment.